Tutoring and Teaching in Undergraduate University Programs - Díaz Barba, Armando Edwin (2024)
This article presents the results of a comparative analysis of student perceptions regarding the effectiveness of tutoring programs at the Universidad Nacional Agraria la Molina (UNALM) and the Universidad César Vallejo (UCV). Through a survey, the following tutorial aspects were evaluated: advice regarding the study plan, academic and professional guidance, monitoring of academic progress, identification of professional goals and skill development, emotional and motivational support, and assistance in solving career-related problems. Significant differences were found between both universities, allowing for the identification of strengths and areas for improvement in each institution’s tutoring programs.